Tomography of Southern California Via Bayesian Joint Inversion of Rayleigh Wave Ellipticity and Phase Velocity From Ambient Noise Cross‐Correlations. Issue 11 (23rd November 2018) - Berg, E. M.; Lin, F.‐C.; Allam, A.; Qiu, H.; Shen, W.; Ben‐Zion, Y.
Abstract: A self‐consistent regional‐scale seismic velocity model with resolution from seismogenic depth to the surface is crucial for seismic hazard assessment. Though Southern California is the most seismically imaged region in the world, techniques with high near‐surface sensitivity have been applied only in disparate local areas and have not been incorporated into a unified model with deeper resolution. In the present work, we obtain isotropic values for Rayleigh wave phase velocity and ellipticity in Southern California by cross‐correlating daily time series from the year 2015 across 315 regional stations in period ranges 6 to 18 s. Leveraging the complementary sensitivity of the two Rayleigh wave data sets, we combine H/V and phase velocity measurements to determine a new 3‐D shear velocity model in a Bayesian joint inversion framework. The new model has greatly improved shallow resolution compared to the Southern California Earthquake Center CVMS4.26 reference model. Well‐known large‐scale features common to previous studies are resolved, including velocity contrasts across the San Andreas, San Jacinto, Garlock, and Elsinore faults, midcrustal high‐velocity structure beneath the Mojave Desert, and shallow Moho beneath the Salton Trough. Other prominent features that have previously only been imaged in focused local studies include the correct sedimentary thickness of the southern Central Valley, fold structure of the Ventura and Oak Ridge Anticlines, and velocity contrast across the Newport‐Inglewood fault. The new shallow structure will greatly impact simulation‐based studies of seismic hazard, especially in the near‐surface low‐velocity zones beneath densely populated areas like the Los Angeles, San Bernardino, and Ventura Basins. Key Points: Ambient noise cross‐correlations across Southern California show clear Rayleigh waves with measurable phase and amplitude information Amplitude information, through Rayleigh ellipticity (H/V), gives new constraint on near‐surface structure due to shallow crust sensitivity Shallow crust structures previously only seen in local studies are recovered regionally via joint inversion of phase velocity and H/V